DETERMINAN MINAT BISNIS PADA MAHASISWA PENDIDIKAN EKONOMI FAKULTAS EKONOMIUNIVERSITAS NEGERI MAKASSAR - SARI, PUSFITA; MUHAMMAD HASAN; M. IHSAN SAID AHMAD (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2023)
This study describes the internal factors and external factors that influence business interest in students of the Economics Education Study Program class of 2017-2018, Faculty of Economics, Makassar State University. The data collection technique used in this research is by conducting interviews and documentation. The data analysis technique used is descriptive qualitative analysis with interactive analysis methods including selecting data, and analyzing data, and verification. The results showed that internal factors and external factors influenced business interest in students of the 2017-2018 Economic Education Study Program, Faculty of Economics, Makassar State University. It can be seen from the internal factors of business interest in the characteristics, that is, not all informants have a confident attitude in starting a business because the shy attitude to appear in public is still dominant; Work experience has a significant effect because marketing and business skills are very important in running a business; on the family background the feedback, motivation, and support from the family of all informants was very positive; all informants have achievement motivation within themselves in doing business; all informants will be more inclined to attend entrepreneurship seminars and try to establish communication with people who have already owned a business long ago in order to gain broader learning about business. While the external factor of business interest is that all informants want a supportive environment to run their business and all informants will gain knowledge from all fields.